2016
DOI: 10.1111/1365-2664.12783
|View full text |Cite
|
Sign up to set email alerts
|

Forest diversity promotes individual tree growth in central European forest stands

Abstract: * Most experimental evidence on the relationship between biodiversity and ecosystem functioning comes from ecosystems with fast-growing plants, such as grasslands. Although forests provide essential ecological services, they have been less well investigated.  * We used dendrochronology to compare the tree radial growth rates of four important timber species in replicated, spatially mapped stands that differed in tree composition and diversity within a central European managed forest.  * Growth rates differed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 50 publications
1
41
1
1
Order By: Relevance
“…These findings will be essential to devise forest management practices that can maximize synergies between wood production and the safeguarding of forest diversity in Europe (Chamagne et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…These findings will be essential to devise forest management practices that can maximize synergies between wood production and the safeguarding of forest diversity in Europe (Chamagne et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…By lending theoretical support from a series of biodiversity–ecosystem functioning studies, Chamagne et al . () and Fujii et al . () found that positive diversity effects on fundamental functions (i.e.…”
Section: Special Focuses: Forest Biodiversity and Ecosystem Services mentioning
confidence: 86%
“…The studies of Chamagne et al . () and Fujii et al . () were conducted in central Europe and Japan, respectively.…”
Section: Special Focuses: Forest Biodiversity and Ecosystem Services mentioning
confidence: 86%
See 2 more Smart Citations